The Googlization of everything : (and why we should worry) - Vaidhyanathan, Siva. (Berkeley : University of California Press, 2011)
Siva Vaidhyanathan examines the ways we have used and embraced Google--and the growing resistance to its expansion across the globe. He exposes the dark side of our Google fantasies, raising red flags about issues of intellectual property and the much-touted Google Book Search. He assesses Google's global impact, particularly in China, and explains the insidious effect of Googlization on the way we think. Finally, Vaidhyanathan proposes the construction of an Internet ecosystem designed to benefit the whole world and keep one brilliant and powerful company from falling into the "evil" it pledged to avoid. --from publisher description
Introduction: the gospel of Google -- "Render unto Caesar": how Google came to rule the web -- Google's ways and means: faith in aptitude and technology -- The Googlization of us: universal surveillance and infrastructural imperialism -- The Googlization of the world: prospects for a global public sphere -- The Googlization of knowledge: the future of books -- The Googlization of memory: information overload, filters and the fracturing of knowledge -- Conclusion: the human knowledge project.
Includes bibliographical references (p. 219-255) and index.
Keywords: Google (Firm); Internet industry -- Social aspects; Internet -- Social aspects